Interaction of memantine with calf thymus DNA: an in-vitro and in-silico approach and cytotoxic effect on the cancerous cell lines. Issue 3 (2nd February 2022) - Ameen, Faisal; Siddiqui, Sharmin; Kausar, Tasneem; Nayeem, Shahid M.; Sarwar, Tarique; Rizvi, Mohammad Moshahid Alam; Rehman, Sayeed ur; Tabish, Mohammad
Abstract: Memantine belongs to the class of cognition enhancers that functions as NMDA receptor antagonist, used to treat Alzheimer's disease. The interaction of memantine with DNA was not investigated. In the present study, the interaction of memantine with ct-DNA, as well as its cytotoxicity on cancer cells, was evaluated. UV-visible spectroscopy, steady-state fluorescence spectroscopic studies revealed the interaction between memantine and ct-DNA. The quenching studies, chemical denaturation, (CD), and DNA melting studies showed the groove binding mode of memantine with ct-DNA. The thermodynamic parameters revealed that the interaction between memantine and ct-DNA is enthalpically driven, and the stabilizing forces involved were hydrogen bonding and van der Waals interaction. The groove-binding was also observed by molecular docking studies, which corroborated the findings of spectroscopic investigations. Density function theory calculations confirmed the existence of electron donor and recipient groups. The stability of memantine and DNA interaction, as well as the critical residues involved in the interaction, was identified by molecular dynamics simulations. Memantine showed cytotoxicity towards the cancer cells as compared to normal cells, as observed by MTT assay. Inverted compound microscopy analysis of memantine treated cancer cell lines further confirmed the results obtained by MTT assay. Communicated by Ramaswamy H. Sarma